The effect of applying the principle of independence on the quality of internal auditing in the Jordanian companies listed on the Amman Stock Exchange - Aljboul, Moyasser Menazel (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to identify the effect of applying the principle of independence on the quality of internal auditing on firms listed at the Amman Stock Exchange. To achieve the objectives of the study, the descriptive analytical approach was followed, and the study sample consist of a sample of (100) of employee in the companies that listed on the Amman Stock Exchange. The most important findings of the study are that there is a strong degree of agreement among the study participants on the extent of applying the principle of independence in the companies listed on the Amman Stock Exchange, and the general mean for its phrases was (3.86). The study also concluded that there is a good and positive degree of agreement on the quality of the internal audit found in the Jordanian firms listed on the Amman Stock Exchange from the viewpoint of workers in companies at a good level, and The general mean for its phrases was (3.35). Finally, the study found that there was a significant effect on applying the principle of independence to the quality of internal audit in the firms listed on the Amman Stock Exchange. And that the application of the principle of independence in the Jordanian companies listed on the Amman Stock Exchange is responsible for enhancing 27.5% of the quality of internal auditing, which is a good and effective percentage.